Experimental exploration of dynamic phase transitions and associated metamagnetic fluctuations for materials with different Curie temperatures (2020)
We study dynamic magnetic behavior in the vicinity of the dynamic phase transition (DPT) for a suitable series of samples that have different Curie temperatures TC, which thus enables us to experimentally explore the role of the reduced temperature T/TC in the DPT. For this purpose, we fabricate Co1-xRux epitaxial thin films with uniaxial in-plane anisotropy by means of sputter deposition in the concentration range 0.0≤x≤0.26. All samples are ferromagnetic at room temperature, exhibit an abrupt magnetization reversal along their easy axis, and represent a unique TC and thus T/TC ratio according to their Ru concentration. The dynamic magnetic behavior is measured by using an ultrasensitive transverse magneto-optical detection method and the resulting dynamic states are explored as a function of the applied magnetic field amplitude H0 and period P, as well as an additional bias field Hb, which is the conjugate field of the dynamic order parameter Q. Our experimental results demonstrate that the qualitative behavior of the dynamic phase diagram is independent of the T/TC ratio and that for all T/TC values we observe metamagnetic anomalies in the dynamic paramagnetic state, which do not exist in the corresponding thermodynamic phase diagram. However, quantitatively, these metamagnetic anomalies are very strongly dependent on the T/TC ratio, leading to an about 20-fold increase of large metamagnetic fluctuations in the paramagnetic regime as the T/TC ratio increases from 0.37 to 0.68. Also, the phase space range in which these anomalous metamagnetic fluctuations occur extends closer and closer to the critical point as T/TC increases. © 2020 American Physical Society.